Tinjauan Rekayasa Genetika Tanaman Menggunakan Bakteri Agrobacterium tumafaciens Sebagai Pengembangan Bioteknologi Modern Dari Periode Lama Hingga Terkini: Review of Plant Genetic Engineering Using the Bacteria Agrobacterium tumafaciens as a Development of Modern Biotechnology from the Old to the Recent Period - Rezaldi, Firman; Arti Wahyu Utami, Arti Wahyu Utami; Ratna Fitry Yenny, Ratna Fitry Yenny; M. Fariz Fadillah, M. Fariz Fadillah; Ucu Wandi Somantri, Ucu Wandi Somantri; Heny Sasmita, Heny Sasmita; Rina Nurmaulawati, Rina Nurmaulawati (Politeknik Negeri Cilacap, 2024)
Transgenic plants are plants produced using modern biotechnology methods, namely genetic engineering. Talking about modern biotechnology which tends towards genetic engineering of plants, so far it uses living things that have the potential or contribution as GMOs. The services of living creatures used to produce plants in the aspect of genetic engineering are the species Agrobacterium agrobacterium which has been widely inserted to increase resistance to disease, produce active ingredients for functional food, medicine and natural cosmetics (pharmaceuticals). So that cultivating plants using the services of Agrobacterium agrobacterium provides a good and potential outlook for the future based on studies of transgenic plants, early studies of Agrobacterium, taxonomic challenges, a surge in basic research driven by applied studies, fundamental process models, and future prospects for genetic engineering modeling systems through the use of Agrobacterium. The long-term application of A. tumafaciens has promising future prospects, although it requires various cellular approach methods to make it safe and controllable as a plasmid vector.